A Cross-Cultural Analysis of the Influence of Timbre on Affect Perception in Western Classical Music and Chinese Music Traditions - Wang, Xin; Wei, Yujia; Heng, Lena; McAdams, Stephen (Frontiers in Psychology, 2021)
Timbre is one of the psychophysical cues that has a great impact on affect perception in cross-cultural research, although it has not been the subject of much research. Our aim is to investigate the influence of timbre on the perception of affect conveyed by Western and Chinese classical music using a cross-cultural approach. Four listener groups (Western musicians, Western nonmusicians, Chinese musicians, and Chinese nonmusicians; 40 per group) were presented with 48 musical excerpts, which included two musical excerpts (one piece of Chinese and one piece of Western classical music) per affect quadrant from the valence-arousal space, representing angry, happy, peaceful, and sad emotions and played with six different instruments (erhu, dizi, pipa, violin, flute, and guitar). Participants reported ratings of valence, tension arousal, energy arousal, preference, and familiarity on a continuous scale ranging from 1 to 9. Analyses of variance (ANOVA) reveal that participants' cultural backgrounds have a greater impact on affect perception than their musical backgrounds, and musicians distinguish between a perceived measure (valence) and a felt measure (preference) more accurately than nonmusicians. We applied linear partial least squares regression (PLSR) to explore the relation between affect perception and acoustic features. The results show that the important acoustic features for valence and energy arousal are similar, which are related mostly to spectral variation, the shape of the temporal envelope, and the dynamic range. The important acoustic features for tension arousal describe the shape of the spectral envelope, noisiness, and the shape of the temporal envelope. The explanation for the similarity of perceived affect ratings between instruments is the similar acoustic features that were caused by the physical characteristics of specific instruments and performing techniques.